1996
DOI: 10.1002/cbf.685
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylated beta‐1,3‐glucan inhibits the binding and degradation of acetylated low density lipoproteins in macrophages In Vitro and modulates their plasma clearance In Vivo

Abstract: In atherosclerotic lesions, macrophages are transformed into foam cells accumulating modified low density lipoproteins (LDL) via the scavenger receptor pathway. We have investigated the effects of carboxymethylated beta-1,3-glucan (CMG) on acetylated LDL (AcLDL) metabolism in murine peritoneal macrophages in vitro and upon the clearance of AcLDL by rat liver in vivo. In cultured murine peritoneal macrophages, CMG reduced substantially the AcLDL-induced synthesis of cholesteryl esters, decreased the binding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Scavenger receptors recognize LDLs (low-density lipoproteins) and fatty acids and are involved in mechanisms of inflammation and atherogenesis but also are able to recognize other molecules such as β-glucans . Further experiments demonstrated that binding of β-glucan to the macrophage scavenger receptor protects against endotoxic shock and weakens the binding of LDL. , Since the uptake of LDL by macrophages is considered one of the initial steps in the formation of atherosclerotic lesions, the use of β-glucans to prevent atherogenic events could be an alternative therapy to be explored.…”
Section: Chapter 1 Biomedical Applications and Properties Of β-Glucansmentioning
confidence: 99%
“…Scavenger receptors recognize LDLs (low-density lipoproteins) and fatty acids and are involved in mechanisms of inflammation and atherogenesis but also are able to recognize other molecules such as β-glucans . Further experiments demonstrated that binding of β-glucan to the macrophage scavenger receptor protects against endotoxic shock and weakens the binding of LDL. , Since the uptake of LDL by macrophages is considered one of the initial steps in the formation of atherosclerotic lesions, the use of β-glucans to prevent atherogenic events could be an alternative therapy to be explored.…”
Section: Chapter 1 Biomedical Applications and Properties Of β-Glucansmentioning
confidence: 99%
“…Published data show that 60-80% of circulating LPS are bound to blood proteins. It should be emphasized that up to 50% of these LPS are bound to low-density lipoproteins (LDL) [2,4,6].…”
mentioning
confidence: 99%